Baccharis trimera (Less.) DC leaf derivatives and eupatorin activities against Leishmania amazonensis - Sahid, Esther Della Nina [UNESP]; Claudino, Josiane Clarice [UNESP]; Oda, Fernando Bombarda [UNESP]; Carvalho, Flávio Alexandre [UNESP]; Santos, André Gonzaga dos [UNESP]; Graminha, Marcia A. S. [UNESP]; Clementino, Leandro da Costa [UNESP] (Taylor & Francis, 2021)
Natural products have been largely explored as treatments for leishmaniasis, neglected diseases with few toxic therapeutic options, as scaffolds for the development of new drugs. Herein, derivatives from the aerial parts of Baccharis trimera (Less.) DC (extract and its fractions) were evaluated against Leishmania amazonensis and macrophage cells. The ethyl acetate extract was fractionated by solid-phase extraction, resulting in eight fractions (F1-F8). Fractions F3-4 were further separated into 149 subfractions; subfraction 148 (IC50-PRO = 1.56 ± 0.1 μg mL−1) was selected for purification and constituent(s) characterization by high-performance liquid chromatography, as well as 1H and 13C nuclear magnetic resonance spectroscopy. The flavonoid eupatorin (3’,5-dihydroxy-4’,6,7-trimethoxyflavone) was identified. This compound was 3.7 times more effective against intracellular amastigotes (IC50-AMA = 1.6 ± 0.1 μM) than amphotericin B and presented low cytotoxicity (CC50 > 100 μM), being almost 62 times more selective for the parasite, showing great potential in drug development for cutaneous leishmaniasis treatment.
Keywords: Baccharis trimera; flavonoid; Leishmaniasis; medicinal plant